Experiences of Elderly Living with Noncommunicable Diseases in Utilizing Health Services in Myanmar During the COVID-19 Pandemic - Chei, Nway Eint; Amnatsatsue, Kwanjai; Chansatitporn, Natkamol; Bunngamchairat, Ariya (Kesmas, 2025)
The COVID-19 pandemic and armed conflicts in Myanmar have intensified the challenges in accessing and utilizing health services, particularly for noncommunicable diseases (NCDs) among older adults. This qualitative study explored the experiences of the elderly with NCDs regarding health service accessibility and utilization in secure areas with fully operational health facilities by conducting in-depth interviews with 20 eligible older adults in Myanmar; data were analyzed using content analysis. Four key themes emerged: NCD service utilization patterns; unmet needs; preferences and hesitancy toward NCD services; and disparities, barriers, and opportunities. The findings revealed widespread underutilization of NCD services due to several factors, including geographic inaccessibility, lack of telemedicine, absence of nearby primary health care, inaccessibility of preferred specialists, quality of care issues, high costs, inadequate communication by providers, and insufficient support for healthcare appointments. In conclusion, strengthening elderly-friendly NCD services in Myanmar requires improving accessibility, affordability, care quality, and communication to reduce unmet needs and support healthy aging.